2019
DOI: 10.1021/acs.jnatprod.9b00336
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of Cycloastragenol and Astragenol by Endophytic Fungi Isolated from Astragalus Species

Abstract: Biotransformation of Astragalus sapogenins (cycloastragenol (1) and astragenol (2)) by Astragalus species originated endophytic fungi resulted in the production of five new metabolites (3,7,10, 12,14) together with 10 known compounds. The structures of the new compounds were established by NMR spectroscopic and HRMS analysis. Oxygenation, oxidation, epoxidation, dehydrogenation, and ring cleavage reactions were observed on the cycloartane (9,19-cyclolanostane) nucleus. The ability of the compounds to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…For metabolite 13 , as in the case of 2 and 6 , an additional oxymethine signal at δ H 3.87 (dd, J = 8.7, 2.5 Hz) was observed, which correlated with a resonance at δ C 65.4 in the HSQC spectrum. Furthermore, the 1 H-NMR spectrum of 13 revealed that one of the 9,19-cyclopropane ring signals (δ H 1.10, H-19a) underwent a significant downfield shift compared to 1 , indicating hydroxylation at the C-11 position as described previously 23 , 26 , 27 . The orientation of C-11(OH) was found to be β based on NOESY cross-peak between H-11 (δ H 3.87) and α-oriented H 3 -30 (δ H 0.84).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…For metabolite 13 , as in the case of 2 and 6 , an additional oxymethine signal at δ H 3.87 (dd, J = 8.7, 2.5 Hz) was observed, which correlated with a resonance at δ C 65.4 in the HSQC spectrum. Furthermore, the 1 H-NMR spectrum of 13 revealed that one of the 9,19-cyclopropane ring signals (δ H 1.10, H-19a) underwent a significant downfield shift compared to 1 , indicating hydroxylation at the C-11 position as described previously 23 , 26 , 27 . The orientation of C-11(OH) was found to be β based on NOESY cross-peak between H-11 (δ H 3.87) and α-oriented H 3 -30 (δ H 0.84).…”
Section: Resultssupporting
confidence: 68%
“…This statement was verified with the HMBC experiment. The hydroxy group at C-12 was determined to be β-oriented for 2 and α-oriented for 6 based on NOESY correlations 26 . Based on this data, the structure of 2 and 6 were identified as 20,25-epoxy-3β,6α,12β,16β,24α-pentahydroxycycloartane and 20,25-epoxy-3β,6α,12α,16β,24α-pentahydroxycycloartane, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Endophytic fungi could act as elicitors to induce the expression of host secondary metabolism-related genes and the subsequent production of new metabolites ( Li et al, 2019 ; de Amorim et al, 2020 ). (3) Biotransformation in endophytic fungal metabolites and host metabolites alters plant metabolite composition ( Tian et al, 2014 ; Maggini et al, 2017 ; Ekiz et al, 2019 ). However, the relationship between endophytic fungi of S. alopecuroides and the bioactive compounds of the host has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput sequencing in this study may provide a partial answer to previous research demonstrating that the active substances of A. membranaceus , such as Astragalus polysaccharides, flavonoids, saponins, and organic acids, are changed by L. plantarum and E. faecium fermentation ( 3 ). Recently, endophytic fungi originating from Astragalus species have been used for the biotransformation of Astragalus sapogenins ( 21 ). A. chinensis -derived endophytic fungi are verified to be bactericides and fungicides ( 22 ).…”
Section: Discussionmentioning
confidence: 99%